2018
DOI: 10.1038/s41598-018-26321-8
|View full text |Cite
|
Sign up to set email alerts
|

Northward shift of the agricultural climate zone under 21st-century global climate change

Abstract: As agricultural regions are threatened by climate change, warming of high latitude regions and increasing food demands may lead to northward expansion of global agriculture. While socio-economic demands and edaphic conditions may govern the expansion, climate is a key limiting factor. Extant literature on future crop projections considers established agricultural regions and is mainly temperature based. We employed growing degree days (GDD), as the physiological link between temperature and crop growth, to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
117
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(131 citation statements)
references
References 46 publications
(51 reference statements)
4
117
0
Order By: Relevance
“…The pooled weather data over the three growing seasons showed slightly higher (6%) rainfall compared to the last thirty years depicting the changing climatic pattern ( Table 2). Increased rainfall during crop growth season in the rainfed areas is predicted to enhance the agricultural production [49]. Results of the present study demonstrated higher forage yield in DMP1 (Figure 1a), probably due to higher N, P, K and micronutrients and organic matter, that improved aggregation and soil structure for better aeration, soil quality and maintained or increased soil pH in acidic soils [50].…”
Section: Forage Yieldmentioning
confidence: 58%
See 1 more Smart Citation
“…The pooled weather data over the three growing seasons showed slightly higher (6%) rainfall compared to the last thirty years depicting the changing climatic pattern ( Table 2). Increased rainfall during crop growth season in the rainfed areas is predicted to enhance the agricultural production [49]. Results of the present study demonstrated higher forage yield in DMP1 (Figure 1a), probably due to higher N, P, K and micronutrients and organic matter, that improved aggregation and soil structure for better aeration, soil quality and maintained or increased soil pH in acidic soils [50].…”
Section: Forage Yieldmentioning
confidence: 58%
“…The pooled weather data over the three growing seasons showed slightly higher (6%) rainfall compared to the last thirty years depicting the changing climatic pattern ( Table 2). Increased rainfall during crop growth season in the rainfed areas is predicted to enhance the agricultural production [49].…”
Section: Forage Yieldmentioning
confidence: 99%
“…Expected climate change will likely promote further northward expansion of crops adapted to warmer climates but also decrease suitability in the areas affected by increasingly higher temperatures and more frequent droughts (Hannah et al, 2013;Iglesias et al, 2011;King et al, 2018;Marx et al, 2017; 10.1029/2019EF001178 Peltonen-Saino, 2009). King et al (2018) suggested that crop suitable growing-degree-days conditions will experience a northward expansion of up to 1,200 km in the boreal regions by the end of the 21st century. However, northward expansion of conditions conducive to agricultural crop production in the boreal regions will be accompanied by the migration of agro-climate zones and crop growing conditions also elsewhere in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing and future climate changes are expected to affect agricultural productivity in large parts of the current farming regions [1,2]. On the other hand, global warming and corresponding northward shifts in growing degree-days might favor the expansion of agriculture into boreal areas [3]. However, the primary soil type in the boreal regions is Podzol, a soil type considered as unattractive for agronomic use [4].…”
Section: Introductionmentioning
confidence: 99%